Heavy Is the Crown: CEOs' Social Interactions and Layoff Decisions - Andrea Bassanini; Eve Caroli; Kevin Geay; Antoine Rebérioux (Institute of Labor Economics (IZA), 2024)
We develop a theory of non-monetary costs incurred by CEOs when deciding about layoffs and test its predictions on French data. Our results support the idea that, being embedded in their social environment, CEOs find it more difficult to fire employees closer to their own workplace. This effect is stronger whenever social interactions are less anonymous in the CEOs' local environment. It is weaker when CEOs live further away from where they work, because of limited exposure to local discontent.
Keywords: J63; M12; M51; R12; 330; CEO; non-monetary costs; layoffs; social embeddedness